História e natureza: memórias, sobrevivências, famílias e relações de poder no Manguezal (Bragança – PA, 1980 a 1990) - CAMPOS, Ipojucan Dias (Universidade Federal do Pará, 2020)
This study concentrated efforts in understanding the relationships of power and consequently the meanings that the workers of the growth of mangroves elaborate of his/her work place, it was like this necessary to interpret the historical senses that the construction of the highway Bragança-Ajuruteua it promoted in the life of the crab collector, once the same transformed existence forms, habits and relationship ways with the nature that there are decades were established. Like this being, the article gathered efforts in understanding those workers’ of the nature daily life as, for instance, their survival strategies inside the coastal ecosystem.